2020
DOI: 10.1097/md.0000000000021833
|View full text |Cite
|
Sign up to set email alerts
|

Rapid thrombelastography predicts perioperative massive blood transfusion in patients undergoing coronary artery bypass grafting

Abstract: Massive blood transfusion (MBT) is a relatively common complication of cardiac surgery, which is independently associated with severe postoperative adverse events. However, the value of using rapid thrombotomography (r-TEG) to predict MBT in perioperative period of cardiac surgery has not been explored. This study aimed to identify the effect of r-TEG in predicting MBT for patients undergoing coronary artery bypass grafting (CABG). This retrospective study included consecutive patients first time un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…4 Despite the clinical significance of acute hemorrhage due to its life-threatening characteristics and the need for urgent preparation of massive transfusion to enable optimal management, the development of a prediction model for massive transfusion during surgery is lacking. Several studies have tried to predict massive transfusion during specific types of high-risk procedures, such as liver transplantation, [5][6][7] cardiac surgery, [8][9][10] placenta previa, 11,12 and spine surgery, 13 but the performances of the prediction models were low, with an area under the receiver operating characteristic curve (AUROC) of 0.65 to 0.84. These low predictive powers may originate from the fact that models developed in previous studies were solely based on preoperative factors without incorporating dynamic intraoperative parameters.…”
Section: Introductionmentioning
confidence: 99%
“…4 Despite the clinical significance of acute hemorrhage due to its life-threatening characteristics and the need for urgent preparation of massive transfusion to enable optimal management, the development of a prediction model for massive transfusion during surgery is lacking. Several studies have tried to predict massive transfusion during specific types of high-risk procedures, such as liver transplantation, [5][6][7] cardiac surgery, [8][9][10] placenta previa, 11,12 and spine surgery, 13 but the performances of the prediction models were low, with an area under the receiver operating characteristic curve (AUROC) of 0.65 to 0.84. These low predictive powers may originate from the fact that models developed in previous studies were solely based on preoperative factors without incorporating dynamic intraoperative parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Because reexploration is a contributor to adverse outcomes, 5 , 6 , 7 , 8 , 9 cardiac surgeons have continued to revise their surgical techniques, and numerous studies have addressed the optimal postoperative management to reduce postcardiotomy bleeding. 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 However, estimating postcardiotomy bleeding is difficult, because it is generally evaluated subjectively by cardiac surgeons. Thus, we attempted to objectively estimate postcardiotomy bleeding during cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 Postcardiotomy reexploration is associated with adverse outcomes, prolonged intensive care unit (ICU) stay, the requirement for an intra-aortic balloon pump, 3 arrhythmias, 5 deep sternal wound infections, 6 , 7 higher mortality rate, longer mechanical ventilation time, higher rate of blood transfusion, 8 and higher costs. 9 To reduce postcardiotomy bleeding complications, many previous studies have reported attempts to prevent the need for reexploration and to reduce the amount of bleeding and blood product consumption after cardiac surgery by adjusting medications 10 , 11 , 12 , 13 or improving perioperative management 14 , 15 , 16 , 17 , 18 ; however, to the best of our knowledge, there is no established methodology for estimating the amount of excessive postcardiotomy bleeding during cardiac surgery. We developed the 5-minute test (FMT), in which the amount of bleeding during cardiac operation is recorded before chest closure.…”
mentioning
confidence: 99%